(3TQM ebGeGJ GdMQjQjs - (3eMeO Hf YHO Gdgd Hf eMeO Hf XaQ Gdecj GdUbdjs; (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s
(3ChdgG (B:s
(3ddg GdeMGeO GdJi fGaJ GdMO hGdeMOhO CeG HYO aEf GdYde CQaY fSH hCf JCKjQ GdYdeGA ai GdCMcGe cJCKjQ GdGdHGH ai GdCLSGe s
(3BNQgG (B:s
(3adbO LdG GdGYJeGO hJdGTi GdJYGXe hGdGSJHOGO agh MSHi hfYe Gdhcjd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(935) s
Keywords: (3GdCOHs